2021
DOI: 10.3390/agriculture11111166
|View full text |Cite
|
Sign up to set email alerts
|

Crop Models: Important Tools in Decision Support System to Manage Wheat Production under Vulnerable Environments

Abstract: Decision support systems are key for yield improvement in modern agriculture. Crop models are decision support tools for crop management to increase crop yield and reduce production risks. Decision Support System for Agrotechnology Transfer (DSSAT) and an Agricultural System simulator (APSIM), intercomparisons were done to evaluate their performance for wheat simulation. Two-year field experimental data were used for model parameterization. The first year was used for calibration and the second-year data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In the current study, the sensitivity of both the APSIM and DSSAT crop models estimated the lower yield predictions by 13.6–38.2% (APSIM) and 7.4–14.7% (DSSAT) for rice under different climate scenarios ( Table 7 ). The current crop production system in most parts of the Indo-Gangetic belt showed a decreasing rice yield trend for both APSIM and DSSAT models [ 36 ]. Moreover, increasing CO2 concentration (571 ppm) will influence the total global average temperature, which will affect rice and wheat yields [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, the sensitivity of both the APSIM and DSSAT crop models estimated the lower yield predictions by 13.6–38.2% (APSIM) and 7.4–14.7% (DSSAT) for rice under different climate scenarios ( Table 7 ). The current crop production system in most parts of the Indo-Gangetic belt showed a decreasing rice yield trend for both APSIM and DSSAT models [ 36 ]. Moreover, increasing CO2 concentration (571 ppm) will influence the total global average temperature, which will affect rice and wheat yields [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, mean wheat yield is likely to increase by 0.8–21.8 per cent (APSIM) and mixed results–decline in wheat yield by 2.9–8.8 per cent (DSSAT). A recent study also suggested that both APSIM and DSSAT yield variabilities for wheat can be managed by strategic management of fertilizer applications in some cases [ 36 ]. Socio-economic analysis for the current study estimated the impact of climate change on future agricultural production systems on farm level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural businesses, academia, NGO's and governments all recognize the issues faced in agriculture and are working toward providing solutions to food security in a sustainable manner, yet the approaches and methods for achieving these goals vary (West et al, 2014). The need for decision support systems that integrate data from farms and provide information for farmers to make decisions has long been recognized (McBratney et al, 2005b;Wajid et al, 2021). However, even with industry led efforts into decision support systems and software, adoption of precision agriculture for efficient application of agricultural inputs remains limited (Schimmelpfennig & Lowenberg-DeBoer, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Decision Support System for Agricultural Technology Transfer (DSSAT) is a crucial tool for agricultural technology transfer and the prospect for DSSAT is really valuable [9]. Using long-term weather and soil data information, it is possible to scale out short-duration field experimental results [10,11].…”
Section: Introductionmentioning
confidence: 99%